Perfil epidemiológico do setor de quimioterapia de um hospital de referência da região norte do Estado do Ceará - Preval, Dafney Marie Madeleine (2023)
Cancer is an important public health problem, presenting significant morbidity and mortality, as well as being associated with significant hospital costs that burden the Unified Health System (SUS). Its epidemiology is also highlighted, where a growing number of cases are observed, reinforcing the importance of early detection and better planning of the referral network in health. The objective of this study is to trace the epidemiological profile of chemotherapy patients at Santa Casa de Misericórdia de Sobral, seeking to provide important data for better organization of the referral system for patients undergoing chemotherapy in the northern region of the state of Ceará. Data collection will be carried out through an investigative questionnaire, between February 2021 and February 2022. In the study, 22 different types of cancer were reported, with a predominance of breast cancer (34.2%), prostate (14.2%), non-solid organ (14.2%), and gastric/stomach (8.5%) cancers. There is a pattern of agreement with national and regional estimates. In women, the most frequent neoplasm is breast cancer, while prostate and stomach cancer were the most representative for men. Thus, it is possible to reaffirm the role of this research and its importance as a strategy for the elaboration of public policies that better serve the population. In this context, breast cancer presents an important epidemiology, adding to the relevance of the epidemiological profile that this disease has been presenting, and thus gaining space in the political and technical agendas of all spheres of government. Among the therapies indicated for oncological treatment, we have chemotherapy, which is associated with important oral side effects. It is hoped that this study can contribute to better protocols of care and greater professional training.